Mengembangkan Penjualan UMKM Alby Key dengan Web E-Commerce - Eri Mardiani; Fachri; Guing Tri Suhatmojo; Kelfin Nurfaizi; Muhammad Rizky Perdana; Prayogo Dwi Cahyo Putro; Salestinus Petrus Dhema; Yoga Dwi Prasetyo (KITA Institute, 2023)
During the pandemic, people are exposed to the risks of in-person trading and tend to switch to digital trading. The purpose of this study is to examine the development of micro, small and medium enterprises (MSMEs) using the waterfall method. The data shows that online sales and purchases have increased significantly, prompting businesses to adopt digital distribution systems. The research highlights the need for community creativity, especially to reduce direct transactions and increase revenues through Internet platforms. In business settings, e-commerce acts as an intermediary for online transactions. Develop online sales and provide features that help buyers improve customer satisfaction and overall sales. The study provides a systematic and sequential overview of how MSMEs are evolving in meeting the challenges of the pandemic, highlighting the importance of adaptation and innovation in digitally enabled trading to business success.